Pressure‐driven, shoreline currents in a perennially ice‐covered, pro‐glacial lake in Antarctica, identified from a LiCl tracer injected into a pro‐glacial stream. Issue 9 (16th October 2014) - Castendyk, Devin; McKnight, Diane; Welch, Kathy; Niebuhr, Spencer; Jaros, Chris
Abstract The distribution of streamwater within ice‐covered lakes influences sub‐ice currents, biological activity and shoreline morphology. Perennially ice‐covered lakes in the McMurdo Dry Valleys, Antarctica, provide an excellent natural laboratory to study hydrologic–limnologic interactions under ice cover. For a 2 h period on 17 December 2012, we injected a lithium chloride tracer into Andersen Creek, a pro‐glacial stream flowing into Lake Hoare. Over 4 h, we collected 182 water samples from five stream sites and 15 ice boreholes. Geochemical data showed that interflow travelled West of the stream mouth along the shoreline and did not flow towards the lake interior. The chemistry of water from Andersen Creek was similar to the chemistry of water below shoreline ice. Additional evidence for Westward flow included the morphology of channels on the ice surface, the orientation of ripple marks in lake sediments at the stream mouth and equivalent temperatures between Andersen Creek and water below shoreline ice. Streamwater deflected to the right of the mouth of the stream, in the opposite direction predicted by the Coriolis force. Deflection of interflow was probably caused by the diurnal addition of glacial runoff and stream discharge to the Eastern edge of the lake, which created a strong pressure gradient sloping to the West. This flow directed stream momentum away from the lake interior, minimizing the impact of stream momentum on sub‐ice currents. It also transported dissolved nutrients and suspended sediments to the shoreline region instead of the lake interior, potentially affecting biological productivity and bedform development. Copyright © 2014 John Wiley & Sons, Ltd.